Analisis Fraud Pentagon dalam Mendeteksi Kecurangan Laporan Keuangan dengan Menggunakan Fraud Score Model - Yudi Partama Putra (UNIVED Press, 2022)
This study aims to determine the effect of Fraud entagon in detecting the fraudulent of financial statements by using Fraud Score Empirical Study Model on property and real estate companies listed on Indonesia Stock Exchange for the periods 2016-2018. Fraud Pentagon is proxied by eight variables which consists of three variables; the pressure elements (Financial target, Financial stability, External pressure), opportunity elements (Nature of industry and Effective monitoring), elements of rationalization (Change in auditors), one a variable from capability element (Change of directors), and a variable of arrogance element (Frequent number of CEO's picture) to financial statement fraud. The sampling technique is purposive sampling with 24 companies. The data analysis used is multiple regression analysis and classic assumptions. The results indicate that the external pressure and nature of industry have significant effects on financial statement fraud. Meanwhile, financial targets, financial stability, ineffective monitoring, change in auditors, change of directors and frequent numbers of CEO's picture have no significant effects on financial statement fraud.